A systematic literature review of place attachment in environments, cities and landscapes - Linfeng, Shi; Wanyi, Yang; Ujang, Norsidah (Jomard Publishing, 2024)
People's place attachment to the environment, cities and landscapes is crucial to improving urban living environments and enhancing the meaning of place. Researchers are conducting theoretical analysis and case practice in this field. However, there is a lack of an overall review of the literature in this field. A systematic literature review can understand the research characteristics and development trends. Therefore, we obtained 1,808 literature data from the Web of Science core collection database and analysis the research status, evolution, research hot spots and development trends. We conduct visual co-authorship, co-occurrence, co-citation and emergence analyses using the bibliometric tools VOSviewer, CiteSpace and Scimago Graphica. This research found that the amount of literature in this area continues to grow and the topics continue to change, from an initial focus on classic topics such as behavioral intentions to more specific topics such as community attachment through more cases.